2018
DOI: 10.1016/j.jgeb.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of rs316019 variants of SLC22A2 with metformin and other drugs- an in silico analysis

Abstract: Metformin is one of the first-line and most widely prescribed drugs to treat type 2 diabetes (T2D). Its clearance from circulation is mostly facilitated by SLC22A2 (OCT2) in the renal cells. SLC22A2 is a polyspecific organic cation transporter and mediate transport of structurally unrelated endogenous and exogenous compounds including many drugs. rs316019 (p.270A > S) is the most common variant of SLC22A2 with a frequency as high as 15% or more in many populations. The 270S form of SLC22A2 clears metformin fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…Many clinical creatinine‐drug interactions can be rationalized by inhibition of MATEs alone ( Figure ), and role of this transporter is supported by clinical genotyping studies ( Table ). Likewise, OCT2 genotype data support its role in creatinine renal disposition ( Table ), together with in silico structural modeling of creatinine interactions with variants of OCT2 37 . Conversely, confidence toward the in vivo role of OAT2 is limited by inconsistent in vitro uptake data from OAT2‐transfected cell lines, 38 limited genetic variability, and lack of drugs known or expected to inhibit OAT2 in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…Many clinical creatinine‐drug interactions can be rationalized by inhibition of MATEs alone ( Figure ), and role of this transporter is supported by clinical genotyping studies ( Table ). Likewise, OCT2 genotype data support its role in creatinine renal disposition ( Table ), together with in silico structural modeling of creatinine interactions with variants of OCT2 37 . Conversely, confidence toward the in vivo role of OAT2 is limited by inconsistent in vitro uptake data from OAT2‐transfected cell lines, 38 limited genetic variability, and lack of drugs known or expected to inhibit OAT2 in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…The rs316009 variant is located in a transcription factor binding motif and is in linkage disequilibrium with the non synonymous variant rs316019 [ 21 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In previous studies, the TT genotype of rs316009 showed an increase response to metformin in comparison to the CC and CT genotypes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the data available, the CT genotype demonstrated a better response to treatment in comparison to the CC genotype ( Table 4 ). The rs316019 is the most common variant of SLC22A2 in many populations and has displayed contradictory results, linked to both decreased and increased renal clearance of metformin in healthy subjects [ 5 , 40 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through in silico analysis, Sajib et al found that substrates fit better to the binding site of the A270 variant as it is more open and has a wider space than the S270 variant [56]. The polymorphism rs316019 (A270S) is associated with reduced or no changes in transport activity.…”
Section: Genetic Polymorphism In the Oct2 Gene (Slc22a2)mentioning
confidence: 99%